FACTORS AFFECTING THE FORMATION OF INNOVATIVE POTENTIAL AND ITS TRANSFORMATION (World Economics and Finance Bulletin, 2023)
In the process of objectively, comprehensively researching the potential of innovation, the problem of identifying and classifying the factors affecting it arises. Despite the fact that this problem is relevant, it has not been sufficiently studied to this day. For this reason, the mazkup article analyzes the factors affecting innovation potential.
Keywords: Innovation economy; innovation potential; innovation process; innovation project